Echocardiographic parameters of the freestyle stentless bioprosthesis in aortic position: the European experience. - Baur, L; Jin, X; Houdas, Y; Peels, C; Braun, J; Kappetein, A; Prat, A; Hazekamp, MG; Van Straten, B; Ploeg, A; Sieders, A; Voogd, P; et al. (1999)
The objective of this study was to determine normal Doppler and 2-dimensional characteristics of the Freestyle stentless aortic bioprosthesis. The Freestyle aortic bioprosthesis is a new type of aortic xenograft, and experience is limited. We therefore determined the normal range of echocardiographic and Doppler examinations of this valve. Three hundred thirty-nine consecutive patients with a Freestyle aortic bioprosthesis underwent an echocardiographic and Doppler examination according to a common protocol. Investigations were done within 4 weeks after operation, after 3 to 6 months, and after 1, 2, and 3 years. With a valve size from 19 to 27 mm, mean gradients decreased from 7.9 +/- 5.1 mm Hg at discharge to 5.5 +/- 3. 8 mm Hg after 3 to 6 months (P <.001). Thereafter, gradients remained stable. Effective orifice area 1 year after implantation was 1.59 +/- 0.58 cm(2) for the 21-mm valves, 1.92 +/- 0.74 cm(2) for the 23-mm valves, 2.03 +/- 0.64 cm(2) for the 25-mm valves, and 2.52 +/- 0.72 cm(2) for the 27-mm valves (P <.001). The performance index, the ratio of the measured effective orifice area in the patient divided by the effective orifice area measured in vitro, increased from 67% +/- 20% at discharge to 82% +/- 29% after 1, 2, and 3 years. Performance index was especially very high in the smaller-sized valves. After implantation with the subcoronary technique or root-inclusion technique, small cavities could be seen between the native aortic root and the Freestyle valve. Doppler values were evaluated for the Freestyle stentless porcine bioprostheses in the aortic root. Gradients appear to be close to those measured in native valves over a time period of 3 years.